Evolving threats: Leveraging C. elegans to decode the virulence profiles of highly related environmental Salmonella Newport isolates - Christina M. Ferreira; Mirae Choe; Bella Wayhs; Julie A. Haendiges; Robert Literman; Jianghong Meng; Arjuman Ghazi; Rebecca L. Bell (PLoS ONE, 2026)
Salmonella enterica subspecies enterica , particularly serovar Newport, remains a leading cause of foodborne illnesses in the United States, implicated in numerous outbreaks associated with a diverse array of food products. This study systematically investigates the virulence of five distinct S . Newport isolates, characterized by varying patterns of pulse-field gel electrophoresis (PFGE) molecular-diagnostic subtyping, using the nematode Caenorhabditis elegans as a host model organism. We conducted viability assays on C. elegans to evaluate how these isolates affect nematode survival. The selected bacterial strains, chosen for their historical significance in foodborne outbreaks yet isolated form environmental sources, were previously sequenced to provide a comprehensive genomic framework. A notable focus of our research was on the nearly genetically identical PFGE types Newport-61 and the Newport-1015 isolates, which differ by a 1.7 Mb genomic inversion. C. elegans survival assays in response to pathogenic-strain infections revealed that one Newport-1015 and the Newport-61 isolates were particularly more virulent compared to other isolates tested. These findings enhance our understanding of the pathogenic potential of environmental S . Newport and highlight the need to understand the regulatory mechanisms that contribute to virulence capacity.